Golden jackal as a new kleptoparasite for Eurasian lynx in Europe - Krofel, Miha; Hočevar, Lan; Fležar, Urša; Topličanec, Ira; Oliveira, Teresa (Global Ecology and Conservation, 2022)
The arrival of a new carnivore can have important effects on local communities. While several effects of introduced alien species have been well documented, few studies have reported the ecological consequences of an expanding native species. Golden jackals (Canis aureus) are rapidly expanding their distribution in Europe, far beyond their historic range. While this raises many concerns about their potential impact on native wildlife, actual consequences are rarely recorded. Besides being a predator, the jackal is also an efficient scavenger and could function as a kleptoparasite for other predators living in areas colonized by jackals. Large felids are among the predators most vulnerable to kleptoparasitism and Eurasian lynx (Lynx lynx) are already known to be negatively affected by several scavengers. Here we report on the first confirmed cases of jackals scavenging on lynx kills in the Dinaric Mountains, Slovenia. We used camera traps to monitor scavengers at 65 lynx kills and recorded two cases of groups of jackals feeding on roe deer killed by lynx. To determine the potential for jackal kleptoparasitism on lynx at the continental level, we also calculated trends in the overlap in distribution ranges of both species in Europe. To date, jackals have colonized 13% of lynx range, including parts of two highly threatened populations. Finally, we highlight the potential impact of sympatric grey wolves (Canis lupus) to modulate this newly described jackal-lynx kleptoparasitic interaction.